An Overview of Grammar Translation Method’s Effect on EFL Teaching And Learning - Aisha Ahmed Ali Hadi Al-maamari (IJET (Indonesian Journal of English Teaching), 2021)
In language teaching and learning, several methods are used for the effectiveness of teaching and learning activity. The researcher implemented the methods to assist the teacher in teaching the language, time after time. The methods have undergone many changes and development based on the attitude and school of thought for teaching and learning a language, so each method has a different character, technique, and implementation. This reflection will expand on the grammatical translation method (GTM) used in the nineteenth century to teach English as a foreign language. This method is based on the goal of grammatical competence. To achieve the goal, this method has several characteristic and technique which will be used in its implementation. The writer attempts to do a review by investigating 5 published articles gathered from internet websites to show the use of the grammar-translation method, its effectiveness, and why it is criticized for teaching and learning English as a foreign language. The writer’s reflection is included too.